2017
DOI: 10.1038/s41598-017-07294-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Prevents Retinal Damage Generated by Optic Nerve Trauma in the Rat

Abstract: Ocular and periocular traumatisms may result in loss of vision. Hypothermia provides a beneficial intervention for brain and heart conditions and, here, we study whether hypothermia can prevent retinal damage caused by traumatic neuropathy. Intraorbital optic nerve crush (IONC) or sham manipulation was applied to male rats. Some animals were subjected to hypothermia (8 °C) for 3 h following surgery. Thirty days later, animals were subjected to electroretinography and behavioral tests. IONC treatment resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
2
20
0
7
Order By: Relevance
“…Fortyfive-day-old rats (n 10 per experimental group) were subjected to electroretinography, as described (Rey-Funes et al, 2017). Briefly, after overnight adaptation in the dark, rats were anesthetized under dim red illumination.…”
Section: Electroretinogramsmentioning
confidence: 99%
“…Fortyfive-day-old rats (n 10 per experimental group) were subjected to electroretinography, as described (Rey-Funes et al, 2017). Briefly, after overnight adaptation in the dark, rats were anesthetized under dim red illumination.…”
Section: Electroretinogramsmentioning
confidence: 99%
“…For instance, it has been widely reported that it is a relatively potent inhibitor of SCD (IC 50 = 0.9 uM). However, SA is also able to mediate anti-inflammatory and protective effects in the retina independently of SCD (AP, RP, APS, IML, in preparation) by a mechanism that could also involve the toll-like receptor 4 (TLR4) receptor and intracellular kinases [58] and could be of interest in other retinal pathologies [120,121].…”
Section: Sa and Therapeutic Opportunitiesmentioning
confidence: 99%
“…In mammals, however, loss of temperature homeostasis, as occurs in hypo-or hyperthermia can have pathological effects on neuronal function, as occurs in febrile seizures in hyperthermia [10]. Experiments in human subjects have also shown that modest changes in body temperature appear able to alter visually-evoked potentials [11] and lowering body temperature has a neuroprotective effect on the survival and function of retinal neurons in a model of optic nerve injury [12].…”
Section: Introductionmentioning
confidence: 99%